Factors affecting the profitability of reinsurance companies in sub-Saharan Africa: Evidence from dynamic panel analysis - Odunayo Magret Olarewaju; Thabiso Sthembiso Msomi (Cogent Business & Management, 2022)
This study, which analysed the profitability of 42 reinsurers in Sub-Saharan Africa from 1991 to 2020, revealed that various factors such as gross domestic product, competition (HHI), premium growth, investment performance, underwriting risk, and operational efficiency affect the profitability in these companies. This study is quantitative and dynamic using system-generalised method of moments to analyse the data. The study discovered that reinsurers should broaden their services to remain highly competitive and boost their premium growth such that their profitability is sustained. Also, there should be a separate department of qualified professionals overseeing the adequate management of risk before sealing ceding agreement with insurers.
Keywords: L25; G21; G32; M41; G22; 650; firm-specific; industry level; macroeconomic; Reinsurance; sub-Saharan Africa; system-generalised method of moments